The Effect Of Compensation And Work Discipline On Employee Performance At PT. Langgeng Baja Pratama In Bekasi Regency - Sudiarto, Sudiarto (Pasundan Social Science Development, 2024)
This study aims to determine the effect of compensation and work discipline on employee performance at PT Langgeng Baja Pratama in Bekasi Regency. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study showed that compensation had a significant effect on employee performance of 50.3%, the hypothesis test obtained t count> t table or (7.788> 2.000). Work discipline had a significant effect on employee performance of 41.0%, the hypothesis test obtained t count> t table or (6.462> 2.000). Compensation and work discipline simultaneously had a significant effect on employee performance with the regression equation Y = 9.869 + 0.416X1 + 0.353X2 and a contribution of 61.3%, the hypothesis test obtained F count> F table or (46.655> 2.760).